PENERAPAN AKUNTANSI LINGKUNGAN DALAM HAL PENGELOLAAN LIMBAH PRODUKSI PADA PT. ANEKA SUMBER TATA BAHARI - Lestaluhu, Maulidya; Janwarin, Xaverius M; Dewi, Syarina Noormala (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2024)
This research aims to find out how environmental accounting is implemented in terms of production waste management at PT. Various Sources of Maritime Management. This research uses qualitative research. The data collection methods used in this research are interviews, observation and documentation. The results of this research explain that PT. Aneka Sumber Tata Bahari has carried out the stages of implementing accounting in accordance with PSAK No.33 revised 2011. This is known based on identification, recognition and measurement, where the company has incurred and recognized waste management costs as well as measuring environmental costs (in terms of waste management ) carried out by PT. Various sources of nautical management use rupiah units, however, when presenting the company's waste management costs as one in the financial statements presented in the profit and loss report, the company should create a special environmental cost account in the profit and loss report. The stages of treating environmental costs as production costs are waste levy costs, waste water testing costs, air waste testing costs, IPAL cleaning, and waste channel repair costs.